1993
DOI: 10.1007/bf00919387
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte subsets in hemodialysis patients treated with recombinant human erythropoietin

Abstract: We investigated whether recombinant human erythropoietin (rhEPO) therapy affected the lymphocyte subsets in patients on long-term maintenance hemodialysis (HD) with severe anemia. Before treatment, the numbers of peripheral blood lymphocyte, CD3+, CD4+, CD8+, and CD20+ cells were decreased in HD patients compared to those in healthy subjects, while the number of CD3+HLA-DR+ cells was increased in HD patients compared to that in healthy subjects. Furthermore, the number of CD4+CD45RA+ (naive T) cells was marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 38 publications
1
14
1
Order By: Relevance
“…rHuEpo therapy in these patients was associated with repair of T cell functions [36,38], probably via indirect mechanisms [39], as well as normalization of proinflammatory and anti-inflammatory cytokine levels [40,41]. The discrepancies in data on dialysis patients, showing in some cases increased antibody response to an administered antigen [19,24], and in others no statistically significant difference in the level of antibodies detected [25] deserve proper attention.…”
Section: Discussionmentioning
confidence: 99%
“…rHuEpo therapy in these patients was associated with repair of T cell functions [36,38], probably via indirect mechanisms [39], as well as normalization of proinflammatory and anti-inflammatory cytokine levels [40,41]. The discrepancies in data on dialysis patients, showing in some cases increased antibody response to an administered antigen [19,24], and in others no statistically significant difference in the level of antibodies detected [25] deserve proper attention.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies 7,8,17,18 referring disturbances in the lymphocyte populations of ESRD, as compared to controls; however, there are few 19 studies about the effect of the HD procedure, by studying these cells immediately before and after HD. Our aim was to evaluate an earlier marker of apoptosis through Annexin-V assay using flow cytometry, in a group of ESRD patients and controls, as well as in a group of patients before and after the HD procedure.…”
Section: Cd4 + T-lymphocytes Apoptosis In Hd Patients 139mentioning
confidence: 99%
“…Various studies show that the presence of rhEPO in the culture of mononuclear cells modulates the levels of pro-and anti-inflammatory cytokines produced by either monocytes or lymphocytes [29][30][31]46] . It seems that rhEPO itself does not influence T lymphocytes proliferation, at least not directly [34] . However, according to Cravedi et al [44] , rhEPO inhibits expansion and proliferation of T lymphocytes by uncoupling IL-2R signaling in vitro.…”
Section: Role Of Erythropoietin and Its Recep-tor In Modulating Immunmentioning
confidence: 93%
“…It has also been demonstrated that rhEPO directly enhances B lymphocytes antibody (IgG, IgM and IgA) production in serum-free medium [33] . However, at that time some authors suggested that rhEPO-induced immunomodulation is mainly dependent on general improvement of patients' condition after few months of rhEPO treatment because an elevation of hematological parameters is accompanied by a simultaneous increase in the number naive T lymphocytes [34] . Expression of EPOR on the surface of granulocytes was first described more than a decade ago pointing towards a possible role of EPO and its receptor in the immune responses.…”
Section: Role Of Erythropoietin and Its Recep-tor In Modulating Immunmentioning
confidence: 99%